Pendidikan Karakter dalam Konteks Digital: Memperkuat Kemandirian dan Keterampilan Sosial - Sadam Fajar Shodiq (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The purpose of this article is to strengthen student independence and social skills by discussing character education in a digital context. Using qualitative research, 45 students from the University of Muhammadiyah Yogyakarta (UMY) provided responses. Through interviews, observation, and document analysis, data was collected. Using techniques of thematic analysis, the data were analyzed. The results of the study indicate that UMY students view character education in a digital context favorably. The use of technology can enhance students' learning independence and aid in the development of their social skills. In addition, self-confidence, motivation, and social support were discovered to influence the effectiveness of character education in a digital context. This research contributes to the advancement of character education in a digital context, with an emphasis on student autonomy and social skills. The research findings can serve as a guide for educational institutions as they develop learning strategies to meet the requirements of students confronting digital challenges